Pengaruh Brand Experience dan Brand Image terhadap Brand Loyalty dengan Brand Trust sebagai Variabel Intervening - Riyanto, Fauzi Andhi (Jurnal Ilmiah Poli Bisnis, 2023)
The purpose of this study was to determine the effect of Brand Experience and Brand Image on Brand Loyalty on Culinary Products Sate Kambing Mas in Kartasura with Brand Trust as an intervening variable in Solo Raya. The research method is explanatory research. In this study, the authors used a quantitative assessment method. This study uses a population of people in Solo Raya who have bought products at Sate Kambing "Mas Di" Kartasura. The data analysis technique in this study used Partial Least Square (PLS) with the help of SmartPLS software. The results of this study Brand experience variables have a positive and significant effect on brand trust. Brand image variables have a positive and significant effect on brand trust. Brand trust variables have a positive and significant effect on brand loyalty. Brand experience variables have a positive and significant effect on brand loyalty. The brand image variable has a positive and significant effect on brand loyalty. The mediation results show that brand trust can positively and significantly mediate between brand experience and brand image on brand loyalty. So there is an influence of Brand Experience and Brand Image on Brand Loyalty in culinary products of mas goat satay in Kartasura with brand trust as an intervening variable in Solo Raya.